Comparison of differentiation gene batteries for migratory mechanosensory neurons across bilaterians. Issue 6 (20th February 2020) - Zhao, Di; Chen, Siyu; Horie, Takeo; Gao, Yimeng; Bao, Hongcun; Liu, Xiao
Abstract: In embryos of distantly related bilaterian phyla, their lateral neural borders give rise to the peripheral nervous system elements, including various mechanosensory cells derived from migratory precursors, such as hair cells and dorsal root ganglion (DRG) neurons in vertebrates, bipolar tail neuron (BTN) in Ciona, chordotonal organ in Drosophila, and AVM/PVM in Caenorhabditis elegans . Developmental genetics studies had revealed a couple of transcription factors (TFs) regulating differentiation of mechanosensory cells shared by vertebrates and arthropods. However, unbiased systematic profiling of regulators is needed to demonstrate conservation of differentiation gene batteries for mechanosensory cells across bilaterians. At first, we observed that in both C. elegans Q neuroblasts and Drosophila lateral neuroectoderm, conserved NPB specifier Msx / vab‐15 regulates Atoh1 / lin‐32, supporting the homology of mechanosensory neuron development in lateral neural border lineage of Ecdysozia . So we used C. elegans as a protostomia model. Single‐cell resolution expression profiling of TFs and genetic analysis revealed a differentiation gene battery ( Atonh1 / lin‐32, Drg11 / alr‐1, Gfi1 / pag‐3, Lhx5 / mec‐3, and Pou4 / unc‐86 ) for AVM/PVM mechanosensory neurons. The worm‐gene battery significantly overlaps with both that of placode‐derived Atonh1 / lin‐32 ‐dependent hair cells and that of NPB‐derived Neurogenin ‐dependent DRG neurons in vertebrates, supporting the homology of molecular mechanisms underlying the differentiation of neural border‐derived mechanosensory cells between protostome and deuterostome. At last, Ciona BTN, the homolog of vertebrate DRG, also expresses Atonh1 / lin‐32, further supporting the homology notion and indicating a common origin of hair cells and DRG in vertebrate lineage. Abstract : GRNs underlying the generation of mechanosensory cells from neural borders across bilaterians. Research Highlights: Regulation of Atonal / lin‐32 by Msx / vab‐15 is a conserved gene regulation circuit underlying the generation of mechanosensory neurons in Ecdysozoa Expression of 90% conserved transcription factors were profiled in trunk neurons of L2 stage Caenorhabditis elegans larvae at the resolution of single cells. Following genetics analysis identified Gfi1/pag‐3, SoxC/sem‐2, and Runt/rnt‐1 as novel regulators of AVM/PVM neurons Both regulators of hair cells and those of dorsal root ganglion (DRG) neurons in vertebrates are significantly enriched in the differentiation gene battery of worm AVM/PVM mechanosensory neurons ( Atonal / lin‐32, Drg11 / alr‐1, Gfi1 / pag‐3, Lhx5 / mec‐3, and Pou4 / unc‐86 ). Bipolar Tail Neurons in Ciona expresses both Atonal / lin‐32 and Neurogenin / ngn‐1, indicating the protovertebrate common origin of the molecular mechanism underlying the differentiation of hair cells and DRG neurons.